Protriptyline improves spatial memory and reduces oxidative damage by regulating NF kappa B-BDNF/CREB signaling axis in streptozotocin-induced rat model of Alzheimer's disease - Tiwari, Virendra; Mishra, Akanksha; Singh, Sonu; Mishra, Sandeep Kumar; Sahu, Kiran Kumari; Parul; Kulkarni, Mahesh J.; Shukla, Rakesh; Shukla, Shubha (Brain Research, 2021)
Antidepressants are well known to exert their role via upregulation of brain derived neurotrophic factor (BDNF). BDNF has been reported to exerts its neuroprotective effect in rodent and primate models as well as in patients of Alzheimer's disease (AD). The aim of our study was to evaluate the effect of protriptyline (PRT), a tricyclic antidepressant, in streptozotocin (STZ)- induced rat model of AD. Total 10 mu l of STZ was injected into each ventricle (1 mg/kg). PRT (10 mg/kg, i.p.) treatment was started 3-day post STZ administration and continued till 21 days. We found that STZ treatment significantly increased pTau, A beta 42 and BACE-1 expression, oxidative stress and neurodegeneration in hippocampus and cortex of adult rats. STZ induced impairment in spatial learning and retention memory was associated with increased WO and reduced CREB and BDNF expression in cortex and hippocampus. Interestingly, PRT treatment significantly reduced pTau, A beta 42 and BACE-1 levels, neurodegeneration, oxidative stress and glial activation, contributing to the improved spatial learning and retention memory in STZ treated rats. Moreover, PRT treatment significantly improved p-ERK/ERK ratio and enhanced BDNF and CREB levels by reducing NFXB and GFAP expression in STZ treated rats. Our data suggest that impaired NFXB and CREB signaling potentially contribute in AD pathogenesis by elevating oxidative stress and neuroinflammation mediated neurodegeneration. Our study has established protriptyline as a multi target molecule in pre-clinical model of AD and further investigations on PRT like molecules could pave way for further development of effective new treatments in neurodegenerative disorders.
Keywords: Alzheimer's disease; antidepressant; BDNF; Memory; Oxidative stress; Protriptyline